Outdoor Workers' Use of Sun Protection at Work and Leisure - Cheryl E. Peters (Safety and Health at Work, 2016)
Background: Outdoor workers are at risk of high ultraviolet radiation exposure, and may have difficulty using sun protection. The objectives were to determine the prevalence of sun protection behaviors in a sample of outdoor construction workers, and to assess which factors predict better sun protection practices. Methods: Participants were recruited via construction unions. Workers answered a questionnaire on demographics, skin cancer risk, sun protection behaviors, and job. Sun protection behavior scores (from questions on sunscreen use, sleeved shirt, hat, shade seeking, sunglasses) were calculated by converting Likert-scale answers to scores from 0 to 4, and taking the mean (separately for work and leisure). Determinants of sun protection behavior scores were examined for work and leisure using generalized linear models. Results: Seventy-seven workers had complete questionnaire data (participation 98%). Sun protection behaviors used most often were hats (79% often/always) and sleeved shirts (82% often/always); least prevalent were shade-seeking (8% often/always) and sunscreen (29% often/always). For both work and leisure scores, the strongest predictor was skin type, with fairer-skinned individuals having higher sun protection behavior scores. Workers had higher scores at work than on weekends. Workplaces that required hats and sleeved shirts for safety purposes had higher protection behavior scores. Conclusion: This high-participation rate cohort helps characterize sun protection behaviors among outdoor workers. Workers practiced better sun protection at work than on weekends, suggesting that workplace policies supportive of sun protection could be useful for skin cancer prevention in the construction industry.